A METHOD OF FORMING THE VALUE ATTITUDE OF STUDENT YOUTH TO THEIR OWN HEALTH BY MEANS OF PHYSICAL CULTURE (Physical Culture and Sport: Scientific Perspective, 2025)
A number of researchers have noted a sharp deterioration in the health and physical fitness of Ukrainian students. The overwhelming majority of students lead a sedentary lifestyle, which takes up to 11 hours of active time per day. Other components of students' healthy lifestyles are also far from being healthful. This situation is a result of urbanization, overloading of curricula with theoretical content, lack of a healthy lifestyle culture in the life world of children and youth, social value of the new as opposed to the established, etc. The result is a loss of efficiency and even the ability to work of the future generation of specialists. Therefore, the urgent task of the scientific community of Ukraine is to form a healthy lifestyle for children and youth. The components of the latter are knowledge, values, and behavior, among which the value, in this case the value of health, is crucial for behavioral change. If a subject does not have a value of health, he or she will not perceive health-related knowledge and will not change health-related behavior. That is why today we have numerous publications devoted to both lifestyle improvement and the formation of a value-based attitude to health in children and youth. However, they all have common shortcomings, which are discussed in the article. The article also proposes a simple but effective method of forming a value-based attitude to health in students through physical education, which differs from others in that it does not try to create conditions or an environment for a student's comfortable existence (because according to the biological program, comfort does not lead a person to change), but offers to use the existing conditions qualitatively, to help students in the process of practice to come to the conclusion that their lifestyle should be changed for the better, to stimulate them to make these changes, to help them make these changes effectively. Some methods of surveying students and individualizing their work during physical education classes are proposed.
Keywords: healthy lifestyle; formation of a value attitude to health; students; teacher; need; value; lifestyle; lifestyle improvement; physical education means